2003
DOI: 10.1046/j.1365-2826.2003.01029.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Serotonin on the Development and Migration of Gonadotropin‐Releasing Hormone Neurones in Rat Foetuses

Abstract: This study used a pharmacological approach to evaluate the consequences of the metabolic perturbations of neurotransmitters on brain development. Pregnant rats received p‐chlorophenylalanine (pCPA), an inhibitor of serotonin (5‐hydroxytryptamine, 5‐HT) synthesis, or saline (control) from the 11th day of gestation once or daily up to the 15th, 17th and 20th day, followed by processing of the forebrain and/or nasal cranium of foetal males and females for high‐performance liquid chromatography of monoamines, radi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0
3

Year Published

2004
2004
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 46 publications
1
34
0
3
Order By: Relevance
“…The crossover from nasal region to CNS is a dramatic change in environment, and it has been suggested that such a pause may ensure appropriate maturation of GnRH-1 neurons, allowing them to respond to new molecular cues (for review, see Wray, 2002). To date, several molecules have been shown to alter the GnRH-1 migratory process, including GABAergic, serotoninergic, and glutamatergic signals (Fueshko et al, 1998;Bless et al, 2000;Simonian and Herbison, 2001;Heger et al, 2003;Pronina et al, 2003a).…”
Section: Functional Analysismentioning
confidence: 99%
“…The crossover from nasal region to CNS is a dramatic change in environment, and it has been suggested that such a pause may ensure appropriate maturation of GnRH-1 neurons, allowing them to respond to new molecular cues (for review, see Wray, 2002). To date, several molecules have been shown to alter the GnRH-1 migratory process, including GABAergic, serotoninergic, and glutamatergic signals (Fueshko et al, 1998;Bless et al, 2000;Simonian and Herbison, 2001;Heger et al, 2003;Pronina et al, 2003a).…”
Section: Functional Analysismentioning
confidence: 99%
“…For example, within the nasal region, neural cell adhesion molecules (NCAM; Gong and Shipley, 1996), netrins (Shu et al, 2000), semaphorins (Gavazzi, 2001), EphB2 (St. John and Key, 2001), NELF (Kramer and Wray, 2000a), and CCK (Giacobini et al, 2004) have been identified to influence, either directly or indirectly, olfactoryvomeronasal axon outgrowth and GnRH-1 neuronal migration. At the nasal forebrain junction/cribriform plate, new molecular players appear, i.e., GABA (Fueshko et al, 1998;Bless et al, 2000), glutamate (Simonian and Herbison, 2001), and serotonin (Pronina et al, 2003); while others disappear, i.e., NELF (Kramer and Wray, 2000a). Several of these molecules have been proposed to regulate entrance of the GnRH-1 neurons into the developing forebrain (Wray, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Following earlier reports that implicated serotonin in the development and migration of GnRH neurons (Pronina et al 2003), a great deal of attention has become focused on the role of serotonin in GnRH release (Moguilevsky & Wuttke 2001, Wada et al 2006. The demonstration of synaptic contacts between the serotoninergic system and the GnRH neurons suggested that serotonin could act directly on GnRH release.…”
Section: Introductionmentioning
confidence: 99%